ANALISIS KELAYAKAN FINANSIAL PEREMAJAAN USAHATANI KELAPA SAWIT DI KABUPATEN LAMPUNG SELATAN - Fayza, Arini Dzuriati; Prasmatiwi, Fembriarti Erry; Sayekti, Wuryaningsih Dwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
Oil palm farming in South Lampung Regency was started in 1997, and as it due to economic age, replanting phase is urgently required. This research aims to analyze the financial feasibility of replanting oil palm farming and its sensitivity to various changes. The research was carried out in Katibung District and Candipuro District, South Lampung Regency, Lampung Province from December 2023 – January 2024, with a sample size of 63 oil palm farmers. The data utilized included both primary data and secondary data. The data were analyzed quantitatively using NPV, IRR, Net B/C, Gross B/C, and Payback Period. Based on the research results, the replanting of oil palm farming is financially feasible to carry out. The sensitivity results show that palm oil production costs increased 5.95 percent, palm oil production drop 37.39 percent, and FFB selling prices fell 47.84 percent, replanting palm oil farming is still financially feasible to carry out. Keywords: feasibility, oil palm, replanting, sensitivity